1996
DOI: 10.1111/j.1526-100x.1996.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Native Semidesert Grasses into Existing Stands of Eragrostis lehmanniana in Southeastern Arizona

Abstract: The semidesert grassland in southern Arizona has changed from a native grassland to a scattered Prosopis juliflora var. velutina (mesquite) woodland with an understory of African Eragrostis lehmanniana (Lehmann lovegrass) on many sites. To determine native grass restoration potential, seven species were direct seeded into E. lehmanniana stands that were left alive, burned, sprayed with an herbicide and then either left standing, or mowed. Initial native grass establishment was limited in the live standing trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
5
24
0
Order By: Relevance
“…Although two studies have demonstrated increased postfire abundance of Lehmann lovegrass (Cable 1965;Martin 1983), our research is consistent with many more studies that find a lack of evidence to support a grass/fire cycle, postulates 3 and 4 (Humphrey and Everson 1951;Pase 1971;Cox et al 1988;Bock and Bock 1992;Biedenbender and Roundy 1996;McGlone and Huenneke 2004;Geiger 2006). In addition, the low diversity found in invaded plots can occur without the effects of fire.…”
Section: Discussionsupporting
confidence: 90%
“…Although two studies have demonstrated increased postfire abundance of Lehmann lovegrass (Cable 1965;Martin 1983), our research is consistent with many more studies that find a lack of evidence to support a grass/fire cycle, postulates 3 and 4 (Humphrey and Everson 1951;Pase 1971;Cox et al 1988;Bock and Bock 1992;Biedenbender and Roundy 1996;McGlone and Huenneke 2004;Geiger 2006). In addition, the low diversity found in invaded plots can occur without the effects of fire.…”
Section: Discussionsupporting
confidence: 90%
“…For slow drying conditions, 1-2, 3-4, and 5-7 rainy days followed by over 6, 7, and over 8 rainless days, respectively, would result in seedling desiccation. These estimates generally agree with data of and Biedenbender and Roundy (1996), in which seedings failed in revegetation studies under fast to moderate drying conditions when initial rain or available water periods of 1-3 days were followed by over 4 days of drought. Consistent rainfall apparently is necessary for these warm-season grasses to establish.…”
Section: Discussionsupporting
confidence: 83%
“…Strategies for reintroducing native grasses into communities dominated by non‐natives include no‐till planting, burning, grazing, applying herbicides, inoculating with mycorrhizae, and impoverishing the soil (Patton et al 1988; Nelson & Allen 1993; Biedenbender & Roundy 1996; Huntsinger et al 1996; Masters et al 1996; Masters & Nissen 1998). In abandoned agricultural fields in California, Stromberg and Kephart (1996) summarized successful restoration methods as ensuring good site preparation (native seedlings worked best in a competition‐free environment), seeding with fresh seed with a high germination rate, and mowing annuals before their seeds mature.…”
Section: Introductionmentioning
confidence: 99%